Scientific Policies and Research Entities in Historical Self-Reflection: Institute of Ethnography SASA - Lukić Krstanović (Serbia), Miroslava (Bulletin of the Institute of Ethnography SASA, 2018)
Analyzing a scientific institution and its protagonists in diachronic perspective also entails different levels of (self)assessment – retrospection, introspection, and extrospection, which also points out to turmoils, stratifications, and contradictions of scientific temporal strategies. In this paper I am interpreting processes of the establishment of normative strategies, institutional politics, construction of collectivities, and individual aspirations at the Institute of Ethnography SASA from 1947 until present. Historical self-reflection encompasses five options through which scientific subjectivities and objectivities were formed and confronted: 1. Routinization of meaningful systems and sliding individual inventiveness; 2. Efficiency of the institutional order and distinctiveness in reaching scientific goals; 3. Determined order and individual agility in the zone of enterprising and skillful activism; 4. Consistency of scientific order and constant dynamics in the zones of public visibility; 5. Verifiability in accordance with institutional standrads and coordinated work at the collegial level. Key words: scientific policies, research entities, history, collectivities, individualism